Dollarization in Sub-Saharan Africa : Experiences and Lessons - Mecagni, Mauro (Departmental Papers; Departmental Paper ;, 2015)
Dollarization-the use of foreign currencies as a medium of exchange, store of value, or unit of account-is a notable feature of financial development under macroeconomically fragile conditions. It has emerged as a key factor explaining vulnerabilities and currency crises, which have long been observed in Latin America, parts of Asia, and Eastern Europe. Dollarization is also present, prominently, in sub-Saharan Africa (SSA) where it remains significant and persistent at over 30 percent rates for both bank loans and deposits-although it has not increased significantly since 2001. However, progress in reducing dollarization has lagged behind other regions and, in this regard, it is legitimate to ask whether this phenomenon is an important concern in SSA. This study fills a gap in the literature by analyzing these issues with specific reference to the SSA region on the basis of the evidence for the past decade.